Germline and somatic mutations in the pathology of pineal cyst: A whole‐exome sequencing study of 93 individuals. Issue 6 (4th May 2021) - Yan, Yuanqing; Martinez, Rebecca; Rasheed, Maria N.; Cahal, Joshua; Xu, Zhen; Rui, Yanning; Qualmann, Krista J.; Hagan, John P.; Kim, Dong H.
Abstract: Background: Pineal cyst is a benign lesion commonly occurring in people of any age. Until now, the underlying molecular alterations have not been explored. Methods: We performed whole exome sequencing of 93 germline samples and 21 pineal cyst tissue samples to illustrate its genetic architecture and somatic mutations. The dominant and recessive inheritance modes were considered, and a probability was calculated to evaluate the significance of variant overrepresentation. Results: By analyzing pineal cyst as a Mendelian disease with a dominant inheritance pattern, we identified 42, 325 rare germline variants, and NM_001004711.1:c.476A>G was highly enriched (FDR<0.2). By analyzing it as a recessive disorder, we identified 753 homozygous rare variants detected in at least one pineal cyst sample each. One STIM2 rare variant, NM_001169117.1:c.1652C>T, was overrepresented (FDR<0.05). Analyzing at a gene‐based level, we identified a list of the most commonlymutated germline genes, including POP4, GNGT2 and TMEM254 . A somatic mutation analysis of 21 samples identified 16 variants in 15 genes, which mainly participated in the biological processes of gene expression and epigenetic regulation, immune response modulation, and transferase activity. Conclusion: These molecular profiles are novel for this condition and provide data for investigators interested in pineal cysts. Abstract : Whole exome sequencing of 93 germline samples and 21 pineal cyst tissue samples was performed to study the molecular mechanism of pineal cysts. A list of overrepresented germline genetic variants and somatic mutations were identified for future validation. ​